Delays in routine childhood vaccinations and their relationship with parental vaccine hesitancy: a cross-sectional study in Wuxi, China. (2nd January 2022) - Wang, Qiang; Xiu, Shixin; Yang, Liuqing; Han, Ying; Huang, Jinxin; Cui, Tingting; Shi, Naiyang; Liu, Minqi; Wang, Xuwen; Lu, Bing; Jin, Hui; Lin, Leesa
ABSTRACT: Objectives: This study aimed to examine childhood vaccination delay, explore the association between vaccination delay and parental vaccine hesitancy, and assess childhood vaccination delays during the coronavirus disease (COVID)-19 pandemic in China. Methods: This cross-sectional survey was conducted in Wuxi City. Participants were recruited from local vaccination clinics. Questionnaires were used to collect information about socio-demographics, vaccine hesitancy, and immunization clinic evaluations. Vaccination records were obtained from the Jiangsu Information Management System of Vaccination Cases. Results: Overall, 2728 participants were included. The coverage for seven category A vaccines (Expanded Program on Immunization (EPI)) was more than 95% at 24 months. The proportion of children vaccinated in a timely manner was the highest for the first dose of the hepatitis B vaccine (91.6%) and the lowest for the Bacillus-Calmette-Guerin vaccine (44.6%). More than 50% of the planned vaccinations were delayed in February and March 2020. The Vaccine Hesitancy Scale scores were not associated with vaccination delay (P = 0.842). Children's vaccination delays were negatively associated with parents who reported convenient access to clinics and satisfaction with immunization services (P = 0.020, P = 0.045). Conclusions: EPI is highly successful in China. Despite vaccination delays due to the COVID-19 pandemic, coverage was recovered after lockdown restrictions were eased.